A study of proximal esophageal baseline impedance in identifying and predicting laryngopharyngeal reflux. Issue 9 (11th February 2020) - Chen, Songfeng; Liang, Mengya; Zhang, Mengyu; Tan, Niandi; Lin, Yuqing; Cao, Peixian; Xiao, Yinglian
Abstract: Background and Aim: Laryngopharyngeal reflux (LPR) is caused by the reflux of gastric contents beyond the esophagus into the larynx and pharynx. However, upper esophageal sphincter (UES) motility and proximal esophagus reflux parameters are poorly studied. This study aims to explore the characteristics of UES motility and reflux parameter among LPR patients. Methods: Patients with laryngopharyngeal symptoms only (L), patients with laryngopharyngeal symptoms and typical esophageal symptoms (L + E), patients with typical esophageal symptoms only (E), and healthy controls (H) were retrospectively included. Physiological profiles were studied and compared among groups using both high‐resolution manometry and pH–impedance monitoring, including UES basal pressure, residual pressure, relaxation duration time, recovery time, the time to nadir pressure, UES length, proximal contractile integral, and proximal mean nocturnal baseline impedance (MNBI). Patients' symptom outcomes were also analyzed. Results: A total of 242 patients were included. Proximal MNBI was significantly lower in patients with both laryngopharyngeal and esophageal symptoms (17 cm above low esophageal sphincter [LES]: L vs L + E vs E vs H = 3689.7 vs 2500.0 vs 3073.0 vs 3996.0; 15 cm above LES: L vs L + E vs E vs H = 3155.9 vs 2553.4 vs 3198.9 vs 2985.2; P < 0.001). Patients responded to proton pump inhibitor treatment also had lower proximal MNBI than those who did not (17 cm above LES: 1834.0 vs 3500.0; 15 cm above LES: 1946.5 vs 3432.6; P < 0.001). Conclusion: Decreased proximal MNBI can not only identify LPR patients but also predict patients' symptom outcomes.